New strategies of treatment of postmenopausal osteoporosis - Sobczuk, Anna; Sobczuk, Katarzyna; Pertyński, Tomasz (Menopause Review/Przegląd Menopauzalny, 2011)
Menopause and lack of estrogens are the most common causes of osteoporosis in women. Consequently, bone mineral density quickly decreases and the risk of fractures raises. In the treatment of postmenopausal osteoporosis, antiresorptive agents (estrogens, bisphosphonates, SERM and calcitonin) are employed. In older women, strontium and parathormone can be useful since they increase the bone formation rate. This article presents benefits from above-mentioned therapies based on genetics and molecular biology and discusses various strategies of osteoporosis treatment in Poland, at different stages of the disease.